PENGEMBANGAN MEDIA PEMBELAJARAN DENGAN APLIKASI MACROMEDIA FLASH PADA MATERI PERUBAHAN WUJUD ZAT TERHADAP MOTIVASI BELAJAR SISWA - Ma’natunnisa Ma’natunnisa; Bq Azmi Syukroyanti; Sukainil Ahzan (P-2623-0291)
The research aims to develop learning media using macromedia flash applications on the subject of 'substance change'. The research was conducted in odd semester from August to September 2018/2019 school year at Woha 2 Junior High School. This study adopted the Sugiyono development model. The instrument used is a media validation questionnaire and student learning motivation. The results of the development were seen from the media feasibility questionnaire from expert I by 80% 'in the proper category' and expert II in the amount of 92% in the category of 'very decent'. The average results of the validity test of media experts and student learning motivation questionnaire, namely 86% are categorized as 'very feasible'.The results of the trial of 15 students gave very good categories and 4 students gave good grades, therefore there were an average questionnaire of student learning motivation that was 86.05% categorized very well. The study concluded that learning media development products with macromedia flash applications were 'very good'.